2013
DOI: 10.1213/ane.0b013e31828098b2
|View full text |Cite
|
Sign up to set email alerts
|

Respiration Signals from Photoplethysmography

Abstract: Pulse oximetry is based on the technique of photoplethysmography (PPG) wherein light transmitted through tissues is modulated by the pulse. In addition to variations in light modulation by the cardiac cycle, the PPG signal contains a respiratory modulation and variations associated with changing tissue blood volume of other origins. Cardiovascular, respiratory, and neural fluctuations in the PPG signal are of different frequencies and can all be characterized according to their sinusoidal components. PPG was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 55 publications
1
78
0
1
Order By: Relevance
“…The photoplethysmogram waveform obtained by pulse oximeters varies during spontaneous breathing. 11,12 Changes in venous return, stroke volume, and respiratory sinus arrhythmia that result from respiratory-induced hemodynamic and autonomic neural modulations produce subtle changes in the photoplethysmogram waveform. 13 Other groups previously have demonstrated that evaluating these respiratory-related fluctuations from the photoplethysmogram signal is both a biologically plausible and technically attainable approach to measuring respiration rate.…”
mentioning
confidence: 99%
“…The photoplethysmogram waveform obtained by pulse oximeters varies during spontaneous breathing. 11,12 Changes in venous return, stroke volume, and respiratory sinus arrhythmia that result from respiratory-induced hemodynamic and autonomic neural modulations produce subtle changes in the photoplethysmogram waveform. 13 Other groups previously have demonstrated that evaluating these respiratory-related fluctuations from the photoplethysmogram signal is both a biologically plausible and technically attainable approach to measuring respiration rate.…”
mentioning
confidence: 99%
“…This low sensitivity is the main reason behind the limited application of PPG in clinical practice, since high sensitivity monitors are desired in the PACU to detect any possible adverse events. An 8% maximal error at detecting breaths in adult volunteers is another reason for the limited clinical application of PPG (47). With the improvement in neural network technology at combining all the contributing factors, the aforementioned sensitivity and specificity can be increased, and PPG may become a standard in future real-time monitoring.…”
Section: Ppg-derived Signal For Rrmentioning
confidence: 99%
“…Respiratory-induced intensity variation (RIIV) is present in the PPG signal baseline [16]. The RIIV is considered to be triggered by skin-blood arterial fluctuations stimulated by the respiratory variations in intrathoracic pressure transmitted to the measurement device by the venous system [17].…”
Section: System Design and Implementationmentioning
confidence: 99%